2013
DOI: 10.1152/ajplung.00392.2012
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate disruption of the pulmonary endothelial barrier via activation of endogenous soluble adenylyl cyclase, isoform 10

Abstract: disruption of the pulmonary endothelial barrier via activation of endogenous soluble adenylyl cyclase, isoform 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…cAMP and cGMP are both constitutively formed by transmembrane and soluble adenylyl or guanylyl cyclases in many cell types (36,48,49), including pulmonary endothelium (29,43), and hydrolyzed by specific phosphodiesterases (PDEs) (7,19). The presence or absence of these PDEs plays a large role in the relative abundance of the cNMPs at a given time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cAMP and cGMP are both constitutively formed by transmembrane and soluble adenylyl or guanylyl cyclases in many cell types (36,48,49), including pulmonary endothelium (29,43), and hydrolyzed by specific phosphodiesterases (PDEs) (7,19). The presence or absence of these PDEs plays a large role in the relative abundance of the cNMPs at a given time.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, activation of exogenous soluble adenylyl cyclases leads to increased cytosolic cAMP. This increase in cytosolic cAMP leads to hyperphosphorylation of the microtubule-associated protein tau and causes its dissociation from microtubules resulting in microtubule breakdown (5,43,44,46,51,52), an effect that is sufficient to disrupt the endothelial cell barrier. Activation of soluble adenylyl cyclases causes endothelial cell rounding, loss of cellular adhesions, generation of interendothelial cell gaps, and tissue edema (51,52,56).…”
mentioning
confidence: 99%
“…However, it is becoming increasingly apparent that cAMP signals within cells are compartmentalized. 29,38 Studies suggest that elevation of cytosolic cAMP disrupts the endothelial barrier. 38,39 In contrast, subplasmalemmal cAMP enhances the phosphorylation of effectors that promote junctional integrity, such as filamin A.…”
Section: Dual Regulation Of Endothelial Cell Barrier Functions In Vivmentioning
confidence: 99%
“…29,38 Studies suggest that elevation of cytosolic cAMP disrupts the endothelial barrier. 38,39 In contrast, subplasmalemmal cAMP enhances the phosphorylation of effectors that promote junctional integrity, such as filamin A. 39 In HUVECs, the NP/GC-A/cGMP pathway may have dual effects on cAMP, depending on the relative expression levels of the cAMP-degrading enzymes PDE3A (cGMP inhibited) and PDE2A (cGMP stimulated), mediating positive versus negative cGMP/cAMP cross talks.…”
Section: Dual Regulation Of Endothelial Cell Barrier Functions In Vivmentioning
confidence: 99%
“…For this and other reasons, buffering acidosis with tris-hydroxymethyl aminomethane but not sodium bicarbonate is recommended in patients with hemodynamic instability. Sayner and colleagues (101,123) showed that bicarbonate in a dose-dependent manner decreased resistance across the pulmonary microvascular endothelial cell monolayer. Furthermore, perfusion of mice lungs ex vivo with bicarbonate increased vascular permeability while increasing osmolality had no effect.…”
Section: Regulation Of Endothelial Barrier By Mechanical Stretchmentioning
confidence: 99%